Are Incentives For R&D Effective? Evidence From A Regression Discontinuity Approach - Raffaello Bronzini; Eleonora Iachini (European Regional Science Association (ERSA), 2012)
This paper contributes to the literature on the effectiveness of R&D incentives by evaluating a unique investment subsidy program implemented in northern Italy. Firms were invited to submit proposals for new projects and only those that scored above a certain threshold received the subsidy. We use a sharp regression discontinuity design to compare investment spending of subsidized firms just above the cut-off score with spending by firms just below the cut-off. For the sample as a whole we find no significant increase in investment as a result of the program. This overall effect, however, masks substantial heterogeneity in the program's impact. On average, we estimate that small enterprises increased their investments by about the amount of the subsidy they received from the program, whereas for larger firms the subsidies appear to have had no additional effect.
Keywords: 330